Development of Basic Teaching Materials for Table Tennis in the Form of Interactive Multimedia for Education Students Sport Development Faculty of Sport Science Padang State University - Andika Prabowo; Septian Raibowo; Miftah Fajrin Rahmi (UNIB Press, 2022)
Based on observations and the results of needs analysis in the field, the learning process for table tennis subjects so far still has many shortcomings and needs to be addressed, the presentation of the material content is very complex and difficult to understand, the learning method used is relatively monotonous and does not utilize available learning media, lecturers are still used as the only source of information, so students become less active and creative. So that the process of achieving learning objectives is a little hampered. The purpose of this research is to develop learning resources and media for students in particular and the wider community in the form of table tennis teaching materials in the form of interactive multimedia. This type of research is research and development using the Lee & Owen development model. The data analysis technique used descriptive qualitative analysis in the form of initial observation data and needs analysis and input. The results of the analysis in the form of validation and testing of the developed product can be reported as follows: (1) media expert validation showed 89.65% results, (2) material expert validation showed 97.22% results, (3) evaluation expert validation showed 68 results, 7%, (4) small group trial data 74.17%, (5) large group trial data 75.19%.